L2F/INESC-ID at SemEval-2019 Task 2: unsupervised lexical semantic frame induction using contextualized word representations - Ribeiro, E.; Mendonça, V.; Ribeiro, R.; Matos, D. M. De; Sardinha, A.; Santos, A. L.; Coheur, L. (Proceedings of the 13th International Workshop on Semantic Evaluation, 2019)
Building large datasets annotated with semantic information, such as FrameNet, is an expensive process. Consequently, such resources are unavailable for many languages and specific domains. This problem can be alleviated by using unsupervised approaches to induce the frames evoked by a collection of documents. That is the objective of the second task of SemEval 2019, which comprises three subtasks: clustering of verbs that evoke the same frame and clustering of arguments into both frame-specific slots and semantic roles. We approach all the subtasks by applying a graph clustering algorithm on contextualized embedding representations of the verbs and arguments. Using such representations is appropriate in the context of this task, since they provide cues for word-sense disambiguation. Thus, they can be used to identify different frames evoked by the same words. Using this approach we were able to outperform all of the baselines reported for the task on the test set in terms of Purity F1, as well as in terms of BCubed F1 in most cases.